THE CURRENT STATUS ANALYSIS OF LANGUAGE COMPETENCE OF PUPILS IN SECONDARY SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Each nation’s cultural level is also determined to a certain extent by literacy level of the representatives of the nation and in this case orthographic skills are also important. Literacy is not only measured by the ability to write words, but also by the ability to write them correctly. This skill is formed and developed in direct connection with all levels of language.